The Sustainability of Paddy Field Tourism: Problems and Control Instruments - Lestari, Novita Dian (Marcapada: Jurnal Kebijakan Pertanahan, 2022)
The growing paddy field tourism trend cannot be separated from the shift in tourist interest towards agritourism. Paddy field tourism is seen as having positive roles. Among others, it can improve the quality of life of farmers, provide educational facilities for tourists, and maintain the indigenous culture of the community. These things indicate the need for efforts to maintain its sustainability. However, recent data show that some paddy fields are beginning to experience physical degradation caused by pressure from tourism activities and developments. This is feared to threaten the sustainability of paddy field tourism. Therefore, it is necessary to imme¬diately take steps to control the spatial use to ensure its sustainability in the future. This study aims to provide suggestions in the form of control instru¬ments for the spatial use and strategies for implementing these instruments in order to support the sustainability of paddy field tourism. The method used was library research with qualitative analysis techniques. The results showed that the incentive-disincentive control instrument met the criteria to support the sustainability of paddy field tourism. However, to support its effectiveness, the strategy of implementing the instrument should be carried out by synergizing spatial planning substance with land data.